Employee experience design aplicado na área comercial: um estudo de caso na empresa Ferm - Wendling, Mauryn Jordana (Universidade do Vale do Rio dos Sinos, 2019)
The present study aimed to improve the employee's experience in the workplace, using the Employee Experience Design, so that the company delivers in an agile way the employee needs for a better performance. The Employee Experience Design aims to make organizations try to create a place where employees really want to be, and not be forced to be. To carry out this research, it has been used the method of Design Science Research, along with case study, through a qualitative research of descriptive strategy. The study was conducted in a company that operates in the production of dairy and milk, located in the State of Rio Grande do Sul. In order to achieve the objectives of this research using the Employee Experience Design, four tools were applied: Map of Empathy, Creation of Persona, Map of the Employee's Journey and Action Plan. Such tools were considered artifacts to obtain knowledge and provide the basis for the analyzes. The study contributes to the construction of an action plan, where it was identified opportunities for improvement that could be implemented in the future by the company studied. As main learning, it was concluded that Employee Experience Design methodology helps to identify the needs of the internal commercial area, such as improving the tools available for the execution of tasks, making the work environment more collaborative, improving communication between sectors and promoting recognition of employees.
Keywords: Employee experience; Design; Empatia; Persona; Jornada do funcionário; Design science research; Empathy; Employee’s journey